Kata “Benih” sebagai Metafora Firman Tuhan: Perspektif Semantik dalam Injil Sinoptik (Jurnal Pendidikan Agama dan Teologi, 2025)
This article analyzes the word “seed” as a metaphor of God's word in Jesus' parables found in the Synoptic Gospels (Matthew, Mark, and Luke) with a semantic approach. The metaphor of “seed” in the context of first-century agriculture is used by Jesus to describe human responses to God's words, which are likened to different types of soil. This study explores the literal, metaphorical, and symbolic meanings of the Greek word σπόρος (sporos), and compares its usage in the three Synoptic Gospels to reveal differences in their narrative emphases. This study shows that the metaphor of “seed” not only describes the dynamics of spiritual growth, but also conveys a theological message about the importance of faith, perseverance, and readiness of heart in receiving God's word. As such, this article offers a new perspective that connects biblical and linguistic studies to deepen the understanding of Jesus' teaching.